2008
DOI: 10.1007/s00285-008-0226-7
|View full text |Cite
|
Sign up to set email alerts
|

Geometric and potential driving formation and evolution of biomolecular surfaces

Abstract: This paper presents new geometrical flow equations for the theoretical modeling of biomolecular surfaces in the context of multiscale implicit solvent models. To account for the local variations near the biomolecular surfaces due to interactions between solvent molecules, and between solvent and solute molecules, we propose potential driven geometric flows, which balance the intrinsic geometric forces that would occur for a surface separating two homogeneous materials with the potential forces induced by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
193
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 83 publications
(197 citation statements)
references
References 82 publications
4
193
0
Order By: Relevance
“…(5) recovers the mean curvature flow used in our earlier construction of minimal molecular surfaces [6]. It reproduces the surface diffusion flow [4] when q = 1 and P = 0. It has been shown that the surface generated with the fourth order geometric PDE demonstrates a morphology distinguished from that obtained with the mean curvature flow.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…(5) recovers the mean curvature flow used in our earlier construction of minimal molecular surfaces [6]. It reproduces the surface diffusion flow [4] when q = 1 and P = 0. It has been shown that the surface generated with the fourth order geometric PDE demonstrates a morphology distinguished from that obtained with the mean curvature flow.…”
Section: Introductionsupporting
confidence: 62%
“…Although the constraint has little impact to most image analysis, in which the spacing h is unit, it does lead to some difficulties in other applications. Typically, alternating direction implicit (ADI) methods are implemented to by-pass the stability constraint in solving high-order PDEs [4]. Another approach used in previous PDE transform is the Fourier pseudospectral method via the fast Fourier transform (FFT).…”
Section: Theory and Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…10,12,36,45,[78][79][80] In this work, we develop a phase-field variational implicitsolvent model (PF-VISM) with the PB electrostatics. It is an alternative to the original VISM that uses a sharp-interface formulation, and it extends our previous work 81,82 that only used the Coulomb-field approximation (CFA) of electrostatic free energy.…”
Section: Introductionmentioning
confidence: 99%